Planning standards and community facilities / Maimon Hussein - Maimon, Hussein (Faculty of Architecture, Planning and Surveying, 1983)
This study looks only into the area of space standards and not the whole range of planning standards. Planning standards by definition encompass those type of standards listed in the planning use, development and capacity.